The Impact of Biophilic Design Building on Human Health and Wellbeing of The Physical Environment in Kuala Lumpur - Ahmad Azan, Arinah Raidah; Ismail, Lokman Hakim (Recent Trends in Civil Engineering and Built Environment, 2022)
Relationship between human-nature environments deteriorate with building development that does not achieve the green building concept. Implementing patterns of biophilic design into the building, while reducing the overall environmental impact on the natural and built environment. This study aims to classify the patterns of biophilic design and to analyse the impact of psychological health and well-being on humans of the physical environment in the case study area. For this purpose, the mix-method that includes both observation and the Perceived Restorativeness Scale (PRS) was designed and applied in KLPAC, a biophilic building. The findings revealed a positive correlation between health and wellbeing of people. It supports the idea that the presence of biophilic patterns has a significant impact on the perceived restorative quality of the environment. The review concludes with a call for more research on the restorative quality of the environment and biophilic design.